Structural and optical properties of solvothermal synthesized nearly monodispersed CdSe nanocrystals. (1st August 2016) - Shahi, A K; Pandey, B K; Singh, B P; Gopal, R
Abstract: Water soluble nearly monodisperse CdSe nanocrystals have been successfully synthesized via aqueous phase solvothermal route in non ionic surfactant glycolic acid ethoxylate 4-non phenyl ether (GAEPE). X-ray diffraction (XRD), field emission scanning electron microscopy (FESEM) and transmission electron microscopy (TEM) are used to determine the phase, structural parameters such as lattice constants, strain, x-ray density and specific surface area, morphology, shape and size distribution, respectively, whereas optical properties are studied by UV-visible absorption and photoluminescence (PL) spectroscopy. All the diffraction peaks of XRD pattern indexed to wurtzite phase of hexagonal system of CdSe and crystallite sizes estimated to be 13–29 nm along some stronger and narrower peaks which is also consistent with TEM measurement while crystallinity and defects have been analyzed with selective area electron diffraction (SAED) pattern. Optical absorption spectrum shows that the as prepared sample exhibits primary and secondary absorption band centered at 2.15 eV and 1.82 eV, respectively, which is blue shifted as compared to bulk value (1.74 eV) of band gap due to quantum confinement effect. Photoluminescence spectrum shows sharp excitonic emission band centered at 583 nm which is nearer to primary band gap energy.